Listening Effort in Hearing Aid Users: Is It Related to Hearing Aid Use and Satisfaction? - Kiliç, Samet; Yiğit, Öznur; Türkyilmaz, Meral D. (Journal of the American Academy of Audiology, 2022)
Background Listening effort is primarily reflective of real-world performance. Therefore, it is crucial to evaluate the listening effort to predict the performance of hearing aid (HA) users in their daily lives.Purpose This study aimed to investigate the relationship between listening effort, daily HA use time, and HA satisfaction.Research Design This is a cross-sectional study.Study Sample Thirty-three bilateral behind-the-ear HA users (17 females and 16 males) between 19 and 37 years were participated. All participants had bilateral, symmetric, moderate sensorineural hearing loss and at least 6 months of experience using HAs. The pure-tone average thresholds (PTA) of the participants' left and right ears were 55.34 ± 4.38 and 54.85 ± 5.05, respectively.Data Collection and Analysis First, daily HA use times of the last 30 days were derived from data logging. Second, participants were asked to fill in the Satisfaction with Amplification in Daily Life Scale questionnaire (SADL). Lastly, participants performed the dual-task paradigm to evaluate listening effort. The dual-task paradigm consisted of a primary speech recognition task that included three different individualized signal-to-noise ratio (SNR) conditions, that is, SNR100, SNR80, and SNR50, which the participant could understand 100, 80, and 50% of the speech, respectively. The secondary task was a visual reaction time task that required participants to press the key in response to a visual probe (an image of a white or red rectangle). Multiple linear regression analyses were used to model the effect of factors (daily HA use time and HA satisfaction) on reaction times (RT) of each three individualized SNR sessions.Results Mean daily HA use time of the participants was 5.72 ± 4.14 hours. Mean RTs of SNR50, SNR80, and SNR100 conditions were 1,050.61 ± 286.49, 893.33 ± 274.79, and 815.45 ± 233.22 ms, respectively. Multiple linear regression analyses showed that daily HA use time and HA satisfaction are significantly related to listening effort in all SNR conditions. For SNR80 condition; F (2,30) = 47.699, p < 0.001, with an adjusted R2 of 0.745.Conclusion As far as we know, this study is the first to demonstrate a strong link between listening effort, daily HA use time, and HA satisfaction. Evaluating listening effort following the HA fitting session may provide preliminary information about the treatment success of HA.
Keywords: hearing aids assistive listening devices; listening effort; hearing aid use; hearing aid satisfaction; dual-task paradigm